2023
DOI: 10.3389/fimmu.2023.1199465
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of prognosis and immunometabolism landscapes in ER+ breast cancer based on a novel lipid metabolism-related signature

Abstract: IntroductionLipid metabolic reprogramming is gaining attention as a hallmark of cancers. Recent mounting evidence indicates that the malignant behavior of breast cancer (BC) is closely related to lipid metabolism. Here, we focus on the estrogen receptor-positive (ER+) subtype, the most common subgroup of BC, to explore immunometabolism landscapes and prognostic significance according to lipid metabolism-related genes (LMRGs).MethodsSamples from The Cancer Genome Atlas (TCGA) database were used as training coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Specifically, we downloaded the datasets GSE16969 ( 13 ) and GSE62019 ( 14 ), as well as single cell sequencing data from GSE201048 ( 15 ) ( Supplementary Table 1 ). Lipid metabolism related pathways (LMRPs) were also sourced from the following PubMed articles: PMID35222371 ( 16 ), PMID36091041 ( 17 ), PMID36860853 ( 18 ), and PMID37469520 ( 19 ) ( Supplementary Table 2 ). The design and workflow of this study are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we downloaded the datasets GSE16969 ( 13 ) and GSE62019 ( 14 ), as well as single cell sequencing data from GSE201048 ( 15 ) ( Supplementary Table 1 ). Lipid metabolism related pathways (LMRPs) were also sourced from the following PubMed articles: PMID35222371 ( 16 ), PMID36091041 ( 17 ), PMID36860853 ( 18 ), and PMID37469520 ( 19 ) ( Supplementary Table 2 ). The design and workflow of this study are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, immune cells can also make use of the ketone bodies produced by the fatty acids oxidation to obtain energy (20). Lipids include phospholipids, cholesterol, triglycerides, fatty acids, and many other types (39)(40)(41)(42). Lipid metabolism includes anabolism and catabolism, and the catabolism is commonly known as b-oxidation (43).…”
Section: Lipid Metabolismmentioning
confidence: 99%